Penerapan Konseling Analisis Transaksional untuk Meningkatkan Kesehatan Mental dan Motivasi Belajar Santri - Sa'diah, Halimatus; Fatih, Khoirul Walid Syifaul (Al-Jadwa: Jurnal Studi Islam, 2023)
Motivation directs students to achieve learning goals at Islamic boarding schools. However, in reality, not all students have good motivation to study. The role of counseling is important in the world of education. Counseling is used as a way to increase student motivation, one of which is using a transactional approach. The aim of this research is to see the effectiveness of increasing the learning motivation of students from the As-Salam dormitory at the Darussalam Islamic Boarding School in Banyuwangi after counseling with a transactional approach. This research uses a qualitative research method with a case study type of research. The sampling technique used purposive sampling technique, with the characteristics of participants having low motivation in studying at the Islamic boarding school. There were four participants involved in this research. Data analysis uses the Miles and Huberman model starting from data reduction, data presentation, verification to drawing conclusions. The results of the research show that students are able to bring awareness to the condition of their behavior in learning and are willing to make changes in their behavior for the better, and have goals in their learning process at the Islamic boarding school